Factors affecting wetland ground beetle (Carabidae) assemblages: how important are habitats, conservation designations and management?. Issue 3 (31st July 2013) - Williams, Christopher D.; Hayes, Margaret; Mc Donnell, Rory J.; Anderson, Roy; Bleasdale, Andy; Gormally, Michael J.; Leather, Simon R.
Abstract We investigated factors affecting wetland carabid diversity and assemblage dynamics as part of the first national survey in the Republic of Ireland. Species richness was significantly different among habitat types and was significantly higher on designated as opposed to undesignated land. However, red‐data‐book species richness was significantly higher on undesignated land, highlighting the importance of land outside the conservation network. This was largely due to the prominence of Carabus clatratus L. outside designated areas and often on high‐disturbance land. Management for species of conservation interest outside of designated areas, and in concert with existing agri‐environment, schemes is apparent. Shannon's entropy was significantly greater on grazed as compared to ungrazed land, further highlighting the importance of management in maintaining high diversity carabid assemblages, which should be included in future conservation plans for ground dwelling invertebrates. Models of diversity partitioning for a number of variables (location, habitat type, perceived habitat quality, designation status and grazing) indicated a significantly lower α (within sites) diversity than would be expected by chance, but significantly higher β diversities, indicating that diversity was significantly structured among rather than within groups of these variables. A multi‐response permutation procedure, however, indicated that carabid assemblage composition was significantly, but weakly, structured in terms of domestic grazing, location and both broad and narrow habitat classifications. This indicates a difference in the significance of the effects of variables on beta‐diversity as assessed through partitioning using a dimensionless value and assessments based on the pairwise dissimilarity matrix.